Recovering from Rape: Practical Advice on Overcoming and Coping with Police, Hospitals and Court for Survivors of Sexual Assault and for Their Families, Lovers and Friends. - Ledray, Linda E. (New York HENRY HOLT AND COMPANY, 1986)
Practical advice on overcoming the trauma and coping with police, hospitals, and the courts for the survivors of sexual assault and their families, lovers, and friends.
Keywords: Health